A method to reduce poverty levels using asset evaluation - La Roche, Pablo (Portafolio, 2012)
Even though poverty affects both developing and developed countries, most of the strategies proposed to eliminate it have not been effective because they only concentrate on increasing income, which is only one indicator of poverty levels. But poverty is much more that lack of income, it is the deteríoration of the quality of life. A proposal to reduce poverty based on the analysis of the five types of assets ís presented. These assets can be natural, social, physical, human and financial. The analysis and quantification of these will permit to develop specific strategies to improve the quality of Iife of the families in a more permanent way.